On the role of internal stresses on the superelastic behaviour of Ti-24Nb (at.%). (15th September 2022) - Hildyard, E.M.; Connor, L.D.; Church, N.L.; Whitfield, T.E.; Martin, N.; Rugg, D.; Stone, H.J.; Jones, N.G.
Abstract: Ti-Nb-based alloys undergo a martensitic transformation that gives rise to superelastic and shape memory behaviours over a wide range of temperatures. The design of such alloys for industrial applications is commonly based around the reported martensite start temperature for a given composition. However, there are significant variations in these values within the literature that remain unexplained using current thermally driven transformation theories. Recently, a marked difference in the transformation behaviour of Ti-24Nb (at.%) in the cold rolled and solution treated conditions has been reported and a stress based mechanism has been postulated to rationalise these results. Here, the veracity of this stress based theory has been investigated through in situ studies of the transformation behaviour of Ti-24Nb (at.%) in the cold rolled condition using synchrotron X-ray diffraction . Upon heating to 350˚C, all αʺ initially present reverted to the β phase by ∼ 300˚C. When cooled from 350˚C, thermally induced martensite was observed below ∼ 270˚C and the intensity of the αʺ peaks increased as the temperature decreased. When loaded at temperatures between -150 and 30˚C, further transformation was observed to occur immediately upon the application of a stress. However, critically, αʺ formed under load was always found to be reversible upon unloading, despite being up to 420˚C below the observed martensite start temperature. This behaviour cannot be accounted for through conventional thermally driven transformation theories for these alloys. Comparison of the stress-strain curves for cold rolled and solution heat treated condition material indicated that their behaviours were similar but offset by a value equivalent to the difference in the critical transformation stress. This offset is readily explained by the total stress-based mechanism proposed and provides further evidence as to its fidelity. Graphical abstract: Image, graphical abstract